Pancreatic mucinous cystic neoplasms: a clinicopathological study of 11 cases and detailed review of literature - Nasir Ud Din; Maha Zubair; Jamshid Abdul-Ghafar; Zubair Ahmad (BMC, 2020)
Abstract Background Mucinous cystic neoplasms (MCNs) of pancreas are relatively rare, occur almost exclusively in middle-aged females, and are overwhelmingly located in the body and tail of the pancreas, histologically show an ovarian type stroma. MCNs are premalignant, low aggressive tumors. Here we describe the clinicopathologic and radiologic features and follow up of cases diagnosed in our practice. We also present a detailed review of recent literature. Materials and methods Based on strict criteria, 11 cases diagnosed between 2002 and 2016 were included in the study. Results All cases were reviewed histologically. Mean and median age was 46.7 and 46 years respectively. All patients were females and 9 out of 11 cases were located in the body and/or tail of the pancreas. Mean tumor size was 8 cm. Grossly, cysts were uni or multilocular and ranged from a few millimeters to several centimeters in diameter. Microscopically, all cases showed characteristic tall columnar, mucin producing epithelium and ovarian type stroma. Atypia was mild in 8 cases and severe in 3 cases. The latter 3 cases were classified as non-invasive MCNs with high grade dysplasia (2 cases) and MCN with an associated invasive carcinoma (1 case). On immunohistochemistry, all cases showed epithelial positivity for cytokeratin AE1/AE3 and stromal positivity for vimentin and smooth muscle actin. Follow up was available in 7 cases. All patients were alive and well with no recurrence. Conclusions Our cases show features similar to those described in other published studies although cases in our series tended to be larger in number. Since these tumors are relatively rare, premalignant and have strict diagnostic criteria, they must always be considered in the differential diagnosis of pancreatic mucinous cystic lesions. Larger studies incorporating greater number of patients and more detailed follow up will help in increasing our understanding of MCNs.